Do mayflies (Ephemeroptera) support a biogeographic transition zone in South America?. (18th May 2020) - Molineri, Carlos; Nieto, Carolina; Dos Santos, Daniel A.; Emmerich, Daniel; Zúñiga, M. del Carmen; Fierro, Pablo; Pessacq, Pablo; Gomez, Daniela; Márquez, Javier A.; Príncipe, Romina E.; Valdovinos Zarges, Claudio; Domínguez, Eduardo
Abstract: Aim: South America is considered a biologically hybrid continent. To the south, the Patagonian region harbours a unique biota strongly related to other southern continents. To the northern portion, tropical and subtropical areas from the Neotropical region show a more complex taxocoenosis related to the Nearctic and Afro‐Oriental regions. The South American Transition Zone (STZ) has been proposed to belong simultaneously to both regions. This work aimed to test the validity of STZ in the light of the distributions of an ancient freshwater taxon. Location: South America. Taxon: Ephemeroptera. Methods: We compiled a dataset including all mayfly species having at least one record in South America (8, 268 records for 661 species). By using the Network Analysis Method (NAM), we analysed the validity and delimitation of the STZ. Results: The distributions of Ephemeroptera give rise to groups of cohesively sympatric species with a clear distinction between Patagonian and Neotropical regions. Although some degree of overlap occurs between them, the overlapping area does not match the STZ to a significant extent. The units of co‐occurring species recovered show that Neotropical groups mainly occupy the STZ. Main conclusions: Almost the entire provinces of Puna, Desert and Paramo are not supported as part of the STZ by mayfly distribution. The transition zone between Patagonian and Neotropical mayfly fauna involves Southern Puna and high Andes (south to 17° S latitude), Monte province, and a narrow portion of Patagonian steppe with Chubut River being the southern limit.